The implementation of dual frequency positioning for ionospheric effects correction - da Silva, Jean Roger; do Nascimento, Guilherme A. G. (The International Hydrographic Review, 2025)
Brazil is located in a tropical region near the equator line, where the solar incidence is more intense. For this reason, the effect of ionospheric refraction on satellite signals is more expressive. In order to mitigate this effect, the use of dual frequency positioning technique is effective in the position solution, reducing distortions caused by ionospheric refraction. In this article, dual frequency GPS data was analyzed, in order to prove its effectiveness in correcting the ionospheric error in comparison with single frequency GPS data.